Monitoring training volume through maximal number of repetitions or velocity-based approach - Sánchez-Moreno, M.; Rendeiro-Pinho, G.; Mil-Homens, P. V.; Pareja-Blanco, F. (International Journal of Sports Physiology and Performance, 2021)
Purpose: This study aimed (1) to analyze the interindividual variability in the maximal number of repetitions (MNR) performed against a given relative load (percentage of 1-repetition maximum [%1RM]) and (2) to examine the relationship between the velocity loss (VL) magnitude and the percentage of completed repetitions with regard to the MNR (%Rep), when the %1RM is based on individual load-velocity relationships. Methods: Following an assessment of 1RM strength and individual load-velocity relationships, 14 resistance-trained men completed 5 MNR tests against loads of 50%, 60%, 70%, 80%, and 90% 1RM in the Smith machine bench-press exercise. The relative loads were determined from the individual load-velocity relationship. Results: Individual relationships between load and velocity displayed coefficients of determination (R2) ranging from .986 to .998. The MNR showed an interindividual coefficient of variation ranging from 8.6% to 33.1%, increasing as the %1RM increased. The relationship between %Rep and the magnitude of VL showed a general R2 of .92 to .94 between 50% and 80% 1RM, which decreased to .80 for 90% 1RM. The mean individual R2 values were between .97 and .99 for all loading conditions. The %Rep when a given percentage of VL was reached showed interindividual coefficient of variation values ranging from 5% to 20%, decreasing as the %Rep increased in each load condition. Conclusions: Setting a number of repetitions had acceptable interindividual variability, with moderate relative loads being adjusted based on the individual load-velocity relationship. However, to provide a more homogeneous level of effort between athletes, the VL approach should be considered, mainly when using individual VL-%Rep relationships.